Reported direction of the guard dogs’ behaviour when guarding various farm animal species (N = 25 farms). - Konstanze Krueger (6750239) (2025)
Based on their first visit to farms with guard dogs, experts reported on the quality of the guard dogs’ behaviour towards various individuals. The dogs showed mostly friendly behaviour towards their owner and towards known persons when the owner was present, while showing mostly dominant behaviour towards external dogs and unknown persons in the absence of the owner (Wilcoxon signed rank tests: N = 25, all p < 0.05). They displayed a larger variety, but mostly neutral behaviour towards various farm animal species, known persons (ab) and in the presence of the owner also towards unknown persons.